Cellular N-myristoyltransferases play a crucial picornavirus genus-specific role in viral assembly, virion maturation, and infectivity - Corbic Ramljak, Irena (PLoS Pathog, 2018)
In nearly all picornaviruses the precursor of the smallest capsid protein VP4 undergoes co-translational N-terminal myristoylation by host cell N-myristoyltransferases (NMTs). Curtailing this modification by mutation of the myristoylation signal in poliovirus has been shown to result in severe assembly defects and very little, if any, progeny virus production. Avoiding possible pleiotropic effects of such mutations, we here used pharmacological abrogation of myristoylation with the NMT inhibitor DDD85646, a pyrazole sulfonamide originally developed against trypanosomal NMT. Infection of HeLa cells with coxsackievirus B3 in the presence of this drug decreased VP0 acylation at least 100-fold, resulting in a defect both early and late in virus morphogenesis, which diminishes the yield of viral progeny by about 90%. Virus particles still produced consisted mainly of provirions containing RNA and uncleaved VP0 and, to a substantially lesser extent, of mature virions with cleaved VP0. This indicates an important role of myristoylation in the viral maturation cleavage. By electron microscopy, these RNA-filled particles were indistinguishable from virus produced under control conditions. Nevertheless, their specific infectivity decreased by about five hundred fold. Since host cell-attachment was not markedly impaired, their defect must lie in the inability to transfer their genomic RNA into the cytosol, likely at the level of endosomal pore formation. Strikingly, neither parechoviruses nor kobuviruses are affected by DDD85646, which appears to correlate with their native capsid containing only unprocessed VP0. Individual knockout of the genes encoding the two human NMT isozymes in haploid HAP1 cells further demonstrated the pivotal role for HsNMT1, with little contribution by HsNMT2, in the virus replication cycle. Our results also indicate that inhibition of NMT can possibly be exploited for controlling the infection by a wide spectrum of picornaviruses.